2015
DOI: 10.1016/j.chembiol.2015.03.017
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the PanD/PanZ Protein Complex Reveals Negative Feedback Regulation of Pantothenate Biosynthesis by Coenzyme A

Abstract: SummaryCoenzyme A (CoA) is an ubiquitous and essential cofactor, synthesized from the precursor pantothenate. Vitamin biosynthetic pathways are normally tightly regulated, including the pathway from pantothenate to CoA. However, no regulation of pantothenate biosynthesis has been identified. We have recently described an additional component in the pantothenate biosynthetic pathway, PanZ, which promotes the activation of the zymogen, PanD, to form aspartate α-decarboxylase (ADC) in a CoA-dependent manner. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 56 publications
1
42
0
Order By: Relevance
“…5 ). Interestingly, the C-terminal portion of PanD identified by Monteiro et al [ 17 ] was one of the possible PanM binding regions identified in our study. Specifically, variations in the motif Ala118 to Ala126 identified by the bar in Fig.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…5 ). Interestingly, the C-terminal portion of PanD identified by Monteiro et al [ 17 ] was one of the possible PanM binding regions identified in our study. Specifically, variations in the motif Ala118 to Ala126 identified by the bar in Fig.…”
Section: Resultssupporting
confidence: 55%
“…These residues form the predicted PanD binding site. The asterisk indicates identifies residue Asn45, which was found to be required for PanM binding to pro-PanD [ 17 ]. The bar atop the sequence on the lower panel spans residues Leu66-Gly76, which was also identified by structural studies to be required for PanZ/PanM:PanD interactions [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PanD is produced as a zymogen (proPanD) that is activated by the PanZ·RCoA complex but is also inhibited by the same complex. 8 RCoA = AcCoA or CoA.…”
mentioning
confidence: 99%
“…We have recently reported the structure of the complex formed between the zymogen of E. coli aspartate α-decarboxylase (proPanD) and its regulatory protein, PanZ. 8 PanD is responsible for the production of β-alanine in the pantothenate biosynthesis pathway, 9 and its catalytic action is dependent upon formation of a covalently bound pyruvoyl group from a serine residue via rearrangement of its peptide backbone. 10 PanZ is required for the in vivo activation of E. coli proPanD, as the uncatalyzed rearrangement is too slow to support growth.…”
mentioning
confidence: 99%